Assessing packaging-related knowledge on the basis of a quantitative study - Lendvai Edina (Élelmiszervizsgálati közlemények, 2021)
Packaging technology is one of today’s rapidly evolving disciplines, with innovative implications for many other disciplines, such as the food industry. Plastics can also be referred to as the materials of the 21st century, without which we could hardly imagine our lives today. Bioplastics are made from raw materials from renewable sources, while degradable plastics are mixtures of plastics made from conventional raw materials and additives that aid degradation. In my qualitative, online study, 513 people answered my questions about what the main function of packaging is, what characteristics a packaging material should possess, foods in which packaging are preferred, whether they had ever encountered environmentally friendly packaging materials. In addition to a lot of useful information, it turned out that Hungarian people are typically ecoconscious on paper, but in reality they do not pay enough attention to it. It is primarily college graduate women between the ages of 46 and 65 who also take environmental and ecological considerations into account when buying food.